AUTOMATED PROJECT MANAGEMENT SYSTEM IN TRANSPORT LOGISTICS - Rusanova, Svitlana (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2023)
The article is a continuation of regular research on project management based on efficient transportation. The purpose of the work is to improve the efficiency of management decision-making in the implementation of projects in transport logistics through the use of automated planning and analysis systems. The object of study is the process of forming organizational support for project management in transport logistics using automated planning and analysis systems for project efficiency. The subject of the study is the practical tools for organizational support of project management in transport logistics using automated systems for planning and analyzing project performance. Methods. In the course of the study, a systematic approach was implemented, general scientific methods were used, including logical analysis, synthesis, induction, deduction, analogy, and modeling. The theoretical and methodological basis of the study is the fundamental provisions of project management, management efficiency theory, scientific works of domestic and foreign scientists on project management at the micro, meso, and macro levels. Given the purpose of the work, several tasks were set and solved, in particular, the applied imperatives of resource and budget planning were outlined on the example of a logistics center based on the Odesa seaport and the project implementation was monitored in Microsoft Project. In terms of resource and budget planning, the expediency of using the method and indicators of the volume utilized is proved. The actual progress of the project against the planned indicators is analyzed. A new project was created using the Microsoft Project software and data entry method. In terms of monitoring, conclusions were drawn on the course of events in the project implementation and the status of implementation by individual types of work was clearly shown. All this made it possible to achieve concrete results. In terms of resource and budget planning, it was determined to what extent there is a deviation from the planned project implementation timeframe. In terms of monitoring, the need to optimize staffing, budget, and time parameters was identified. The essence of this optimization boils down to the decision to attract additional labor resources with the corresponding cost of work per hour. This made it possible to get rid of the conflict and obtain positive dynamics in the project implementation, as evidenced by the date of its completion, which remained unchanged after the resources were equalized. The need to continue the study and focus on project risk management is outlined.